Environment-based learning and global citizenship orientation in elementary social studies classrooms - Marsini; Ida Wahyu Wijayati (Jurnal Cakrawala Pendidikan, 2026)
This study examines the effects of environment-based learning and global citizenship orientation on environmental awareness and social studies achievement in Indonesian elementary schools. Using a quantitative ex post facto correlational design, the study involved 180 fourth- and fifth-grade students, selected through cluster random sampling from four schools in Magetan, Indonesia. Data were collected using validated instruments, including scales of environment-based learning, global citizenship orientation, and environmental awareness, as well as a social studies achievement test. The data were analyzed using descriptive statistics, Pearson's correlation, and multiple regression. The results show that environment-based learning and global citizenship orientation significantly predict environmental awareness (R² = .440; p < .001) and social studies achievement (R² = .212; p < .001). Both variables influence affective outcomes more than cognitive performance. This study provides empirical evidence from the elementary school context and highlights the importance of integrating contextual environmental learning and global citizenship education to support students’ holistic development.